Genetic architecture of seed glycerolipids in Asian cultivated rice. (21st June 2022) - Hong, Jun; Rosental, Leah; Xu, Yang; Xu, Dawei; Orf, Isabel; Wang, Wengsheng; Hu, Zhiqiang; Su, Su; Bai, Shaoxing; Ashraf, Mohammed; Hu, Chaoyang; Zhang, Changquan; et al.
Abstract: Glycerolipids are essential for rice development and grain quality but its genetic regulation remains unknown. Here we report its genetic base using metabolite‐based genome‐wide association study and metabolite‐based quantitative traits locus (QTL) analyses based on lipidomic profiles of seeds from 587 Asian cultivated rice accessions and 103 chromosomal segment substitution lines, respectively. We found that two genes encoding phosphatidylcholine (PC):diacylglycerol cholinephosphotransferase (OsLP1) and granule‐bound starch synthase I (Waxy) contribute to variations in saturated triacylglycerol (TAG) and lyso‐PC contents, respectively. We demonstrated that allelic variation in OsLP1 sequence between indica and japonica results in different enzymatic preference for substrate PC‐16:0/16:0 and different saturated TAG levels. Further evidence demonstrated that OsLP1 also affects heading date, and that co‐selection of OsLP1 and a flooding‐tolerant QTL in Aus results in the abundance of saturated TAGs associated with flooding tolerance. Moreover, we revealed that the sequence polymorphisms in Waxy has pleiotropic effects on lyso‐PC and amylose content. We proposed that rice seed glycerolipids have been unintentionally shaped during natural and artificial selection for adaptive or import seed quality traits. Collectively, our findings provide valuable genetic resources for rice improvement and evolutionary insights into seed glycerolipid variations in rice.